N transfer from green manures to lettuce in an intercropping cultivation system - doi: 10.4025/actasciagron.v33i4.6766 - Rogério Haruo Sakai; Edmilson José Ambrosano; Ana Clarissa Alves Negrini; Paulo Cesar Ocheuze Trivelin; Eliana Aparecida Schammass; Paulo César Tavares de Melo (Acta Scientiarum. Agronomy, 2011)
The aim of this work was to evaluate the transfer of N via biological nitrogen fixation from green manures to intercropped lettuce using the 15N abundance method. The treatments consisted of lettuce with black oats, lettuce with cowpea, lettuce with white lupin and monocropped lettuce (control). Green manures were sown at two different times including the following: 60 days before transplanting of lettuce seedlings and simultaneous to transplanting of lettuce seedlings. N transfer was estimated using the natural 15N abundance method. It was observed that lettuce intercropped with green manures reached the same fresh mass of monocropped lettuce when the green manures were sown at the same time as the vegetables were planted. However, when the green manures were sown previously, the fresh mass of the monocropped lettuce was higher, and independent of the sowing time of green manures, the monocropped lettuce reached a higher dry mass. White lupin and cowpea transferred higher amounts of N regardless of sowing time, and the C:N ratio of white lupin to cowpea was lower compared to black oats. Intercropping with white lupin, cowpea and black oat transferred 18, 17 and 7% of N, respectively, to lettuce.